2010
DOI: 10.1111/j.1600-0854.2010.01060.x
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Targeting of an Endosomal E3 Ubiquitin Ligase

Abstract: Ring finger protein 13 (RNF13) is an E3 ubiquitin ligase embedded in endosome membranes. The protein undergoes constitutive post-translational proteolysis, making its detection difficult unless cells are incubated with a proteasome inhibitor to allow biosynthetic forms to accumulate. When cells were treated with phorbol 12-myristate 13-acetate (PMA), RNF13 avoided proteolysis. A similar stabilization was seen on ionomycin treatment of cells. Drug treatment stabilized both the full-length protein and a membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 42 publications
(76 reference statements)
3
26
0
Order By: Relevance
“…Indeed, other RING E3 ligases similar to STRF1 location have been identified in mammals. They include, among others, Tal1, which mediates Tsg101 ubiquitination and cargo sorting into vesicles (Amit et al, 2004) and RNF13, which localizes to the endosome membrane, and may take part in the ubiquitin-mediated endosome/lysosome recycling system (Bocock et al, 2009(Bocock et al, , 2010(Bocock et al, , 2011. Until now, only one E3 ligase from Arabidopsis, KEG (KEEP ON GOING), has been reported to localize to the TGN/EE, and to regulate endocytic trafficking and/or the formation of signaling complexes on TGN/EE vesicles during stress responses (Gu and Innes, 2011).…”
Section: Strf1 Is a Plasma Membrane Protein And An Endosomal E3 Ligasementioning
confidence: 99%
“…Indeed, other RING E3 ligases similar to STRF1 location have been identified in mammals. They include, among others, Tal1, which mediates Tsg101 ubiquitination and cargo sorting into vesicles (Amit et al, 2004) and RNF13, which localizes to the endosome membrane, and may take part in the ubiquitin-mediated endosome/lysosome recycling system (Bocock et al, 2009(Bocock et al, , 2010(Bocock et al, , 2011. Until now, only one E3 ligase from Arabidopsis, KEG (KEEP ON GOING), has been reported to localize to the TGN/EE, and to regulate endocytic trafficking and/or the formation of signaling complexes on TGN/EE vesicles during stress responses (Gu and Innes, 2011).…”
Section: Strf1 Is a Plasma Membrane Protein And An Endosomal E3 Ligasementioning
confidence: 99%
“…Traf6 also interacts with various protein kinases including IRAK1/IRAK, SRC and PKCzeta, which provides a link between distinct signaling pathways. In addition, RNF13 (NP_009213), an integral membrane-associated RING-E3, is targeted to the inner nuclear membrane through recycling endosomes, and has the potential to turn over key nuclear proteins in response to signals received at the plasma membrane [58].…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have reported that RNF13 is present in the endosomal and lysosomal compartments, and the C-terminal region containing the RNF domain is released into the cytosol by proteolytic cleavage [125]. Activation of protein kinase C inhibits this cleavage and stabilizes the full-length RNF13 [127]. The stabilized RNF13 is then transported to the inner nuclear membrane via the recycling endosomes, thereby exposing its RNF domain to the nucleoplasm.…”
Section: Cellular Functions Of the Transmembrane Rnf Proteinsmentioning
confidence: 99%
“…The stabilized RNF13 is then transported to the inner nuclear membrane via the recycling endosomes, thereby exposing its RNF domain to the nucleoplasm. RNF13 may modulate gene expression and signal transduction by mediating ubiquitination in response to various stimuli [35,127]. It is imperative to identify the RNF13 substrate proteins to obtain a better understanding of the physiological role and mechanism of action of RNF13.…”
Section: Cellular Functions Of the Transmembrane Rnf Proteinsmentioning
confidence: 99%